Organizational and pedagogic conditions of maturing the readiness of future pedagogues to work with labour mignrants' children - Nataliia Sabat (Vasyl Stefanyk Precarpathian National University, 2017)
The article substantiates necessity and suitability of marking out the organizational and pedagogic conditions ensuring efficiency of formation of the future pedagogues for work with labour migrants' children. The author has singled out and described the following groups: regulatory provisions representing a complex of normative base regulating the process of  formation of the future teachers; interdisciplinary integration of the educational disciplines aiming to ensure the  integrity and the cross-match of preparation of the future teachers for work with labour migrants' children; Human Resourcing; introduction of the newest teaching technologies within the process of professional formation of the future teachers. Key words: organizational and pedagogic conditions; readiness to professional activity; future pedagogues; labour migrants' children.